Respuesta :

Solution:

We know that:

  • [tex]x - 11 \space\ and \space\ 2x + 8 \space\ are \space\ a \space\ linear \space\ pair. \space\ (Refer \space\ to \space\ attachment.)[/tex]

This means that:

  • [tex](x - 11) + (2x + 8) = 180[/tex]

Step-by step calculations:

Open the parenthesis:

  • [tex](x - 11) + (2x + 8) = 180[/tex]
  • => [tex]x - 11 + 2x + 8 = 180[/tex]

Combine like terms:

  • => [tex]x - 11 + 2x + 8 = 180[/tex]
  • => [tex](x + 2x) + (-11 + 8) = 180[/tex]

Simplify the LHS:

  • => [tex]3x - 3 = 180[/tex]

Add 3 both sides:

  • => [tex]3x - 3 = 180[/tex]
  • => [tex]3x - 3 + 3 = 180 + 3[/tex]
  • => [tex]3x = 183[/tex]

Divide 3 both sides:

  • => [tex]\frac{3x}{3} = \frac{183}{3}[/tex]
  • => [tex]x = 61[/tex]
Ver imagen Аноним

Same side exterior angles are linear pair and have sum 180°

[tex]\\ \rm\Rrightarrow x-11+2x+8=180[/tex]

[tex]\\ \rm\Rrightarrow 3x-3=180[/tex]

[tex]\\ \rm\Rrightarrow 3x=183[/tex]

[tex]\\ \rm\Rrightarrow x=61[/tex]